Fabrikasi Modul Termoelektrik Generator (TEG) menggunakan Semikonduktor Tipe-p SbTe dan Tipe-n BiTe: Melania Suweni Muntini, Meylusari Maghfirotul Afiyanti, Faisal Fikri Oktaviantoni, Wanacaporn Namhongsab, Surasak Ruamrukb, Nattee Khottummee, Tosawat Seetawa - Melania Suweni Muntini Melania Suweni Muntini; Meylusari Maghfirotul Afiyanti Meylusari Maghfirotul Afiyanti; Faisal Fikri Oktaviantoni Faisal Fikri Oktaviantoni; Wanacaporn Namhongsab Wanacaporn Namhongsab; Surasak Ruamrukb Surasak Ruamrukb; Kunchit Singsoogb Kunchit Singsoogb; Nattee Khottummee Nattee Khottummee; Tosawat Seetawan Tosawat Seetawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
This research has been conducted to obtain the value of the best output voltage, output power and efficiency parameters from thermoelectric. Parameter values are obtained from testing and modeling the thermoelectric generator module. The thermoelectric generator module is composed of one pair of p-type SbTe and n-type BiTe p-semiconductors. The tests were done by used an open circuit (no load) and closed circuit (with a load) of 1. The test is done twice for the open circuit and three times for the closed circuit. Furthermore, TEG module was modeled using Ansys 19.2 Academic and Solidworks 2013. Modeling was conducted too in an open and closed circuit using parameter values as in the test. The results of testing and modeling of the highest measurement output voltage for open and closed circuits were obtained at temperatures of 100.770 C and 100.350 C, respectively. The maximum efficiency value is obtained 2.751% with a voltage of 19.2 mV.